2018
DOI: 10.2147/copd.s164671
|View full text |Cite
|
Sign up to set email alerts
|

The role of plasma N-terminal brain natriuretic pro-peptide in diagnosing elderly patients with acute exacerbation of COPD concurrent with left heart failure

Abstract: IntroductionAcute exacerbation of COPD (AECOPD) and left heart failure (LHF) commonly exist together in clinical practice. However, the identification of AECOPD concurrent with LHF is currently challenging. Our study aimed to investigate the role of plasma N-terminal brain natriuretic pro-peptide (NT-proBNP) in diagnosing elderly patients with AECOPD associated with LHF.Methods and resultsLHF was diagnosed in patients with AECOPD according to echocardiographic criteria, and the levels of NT-proBNP in plasma we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…[ 23 24 ] Moreover, the plasma concentrations of NT-proBNP are markedly increased in patients with COPD exacerbation and left ventricular failure compared with those in patients with COPD exacerbation alone. [ 25 ] We suggest that BNP/NT-proBNP tests should be used for performing differential diagnosis in patients with undifferentiated diagnosis presenting with dyspnea and in patients with both COPD and CHF to help distinguish whether the patient primarily has an exacerbation of CHF or that of COPD.…”
Section: 3 Laboratory Testsmentioning
confidence: 99%
“…[ 23 24 ] Moreover, the plasma concentrations of NT-proBNP are markedly increased in patients with COPD exacerbation and left ventricular failure compared with those in patients with COPD exacerbation alone. [ 25 ] We suggest that BNP/NT-proBNP tests should be used for performing differential diagnosis in patients with undifferentiated diagnosis presenting with dyspnea and in patients with both COPD and CHF to help distinguish whether the patient primarily has an exacerbation of CHF or that of COPD.…”
Section: 3 Laboratory Testsmentioning
confidence: 99%
“…Therefore, relationship between NT-proBNP plasma levels, comorbidity and diagnostic cutoff is still a matter of debate. Guo et al [5] evaluated the role of plasma NT-proBNP in diagnosing elderly patients with acute exacerbation of chronic obstructive pulmonary disease (COPD) and HF. They concluded that NT-proBNP diagnostic cutoff of 1,677 ng/L is suggestive of presence of HF associated with COPD.…”
Section: Editorial Article Open Accessmentioning
confidence: 99%